Surface and morphology analyses, and voltammetry studies for electrochemical determination of cerium(iii) using a graphene nanobud-modified-carbon felt electrode in acidic buffer solution (pH 4.0 ± 0.05). Issue 61 (9th October 2020) - Ravi, Pavithra V.; Thangadurai, Daniel T.; Nehru, Kasi; Lee, Yong Ill; Nataraj, Devaraj; Thomas, Sabu; Kalarikkal, Nandakumar; Jose, Jiya
Abstract : GNB-modified – CF electrode was utilized to determine Ce 3+ with LoD ca. 2.60 μM. Abstract : Trace determination of radioactive waste, especially Ce 3+, by electrochemical methods has rarely been attempted. Ce 3+ is (i) a fluorescence quencher, (ii) an antiferromagnet, and (iii) a superconductor, and it has been incorporated into fast scintillators, LED phosphors, and fluorescent lamps. Although Ce 3+ has been utilized in many industries due to its specific properties, it causes severe health problems to human beings because of its toxicity. Nanomaterials with fascinating electrical properties can play a vital role in the fabrication of a sensor device to detect the analyte of interest. In the present study, surfactant-free 1, 8-diaminonaphthalene (DAN)-functionalized graphene quantum dots (DAN-GQDs) with nanobud (NB) morphology were utilized for the determination of Ce 3+ through electrochemical studies. The working electrode, graphene nanobud (GNB)-modified-carbon felt (CF), was developed by a simple drop-coating method for the sensitive detection of Ce 3+ in acetate buffer solution (ABS, pH 4.0 ± 0.05) at a scan rate of 50 mV s −1 using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. CV and DPV studies validated the existence of distinctive peaks at approximately +0.20 and +0.93 V ( vs. SCE), respectively, with a limit of detection of approximately 2.60 μM. Furthermore, electrochemical studies revealed that the GNB-modified-CF electrode was (i) stable even after fifteen cycles, (ii) reproducible, (iii) selective towards Ce 3+, (iv) strongly pH-dependent, and (v) favored Ce 3+ sensing only at pH 4.0 ± 0.05. Impedance spectroscopy results indicated that the GNB-modified-CF electrode was more conductive (1.38 × 10 −4 S m −1 ) and exhibited more rapid electron transfer than bare CF, which agrees with the attained Randles equivalent circuit. Microscopy (AFM, FE-SEM, and HR-TEM), spectroscopy (XPS and Raman), XRD, and energy-dispersive X-ray (EDX) analyses of the GNB-modified-CF electrode confirmed the adsorption of Ce 3+ onto the electrode surface and the size of the electrode material. Ce 3+ nanobuds increased from 35–40 to 50–55 nm without changing their morphology. The obtained results provide an insight into the determination of Ce 3+ to develop an electrochemical device with low sensitivity.